Eight years of the East African Community Medicines Regulatory Harmonization initiative: Implementation, progress, and lessons learned. - Jane H Mashingia; Vincent Ahonkhai; Noel Aineplan; Aggrey Ambali; Apollo Angole; Mawien Arik; Samvel Azatyan; Peter Baak; Emmanuel Bamenyekanye; Aimable Bizoza; Chimwemwe Chamdimba; Petra Doerr; et al. (PLoS Medicine)
Jane H. Mashingia and colleagues reveal the progress made to date for the East African Community Medicines Regulatory Harmonization initiative.